2015
DOI: 10.1038/sc.2014.241
|View full text |Cite
|
Sign up to set email alerts
|

Chemodenervation for treatment of limb spasticity following spinal cord injury: a systematic review

Abstract: Study design: Systematic review. Objectives: To systematically review the literature on chemodenervation with botulinum toxin (BoNT) or phenol/alcohol for treatment of limb spasticity following spinal cord injury (SCI). Setting: British Columbia, Canada. Methods: EMBASE, MEDLINE, CINAHL, Cochrane Database of Systematic Reviews and Cochrane Central Register of Controlled Trials were searched for English language studies published up until March 2014. Studies were assessed for eligibility and quality by two inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Furthermore, spasticity of these regions prevents patients from benefitting from an efficient therapeutic rehabilitation program. In a systematic review by Lui et al [1], three of the four studies reported a decrease in spasticity after chemical neurolysis with phenol/alcohol. The present study revealed significant improvements in the MAS scores of the hip flexion and knee extension muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, spasticity of these regions prevents patients from benefitting from an efficient therapeutic rehabilitation program. In a systematic review by Lui et al [1], three of the four studies reported a decrease in spasticity after chemical neurolysis with phenol/alcohol. The present study revealed significant improvements in the MAS scores of the hip flexion and knee extension muscles.…”
Section: Discussionmentioning
confidence: 99%
“…More than 70% of people with spinal cord injury (SCI) have spasticity and it can have a disturbing effect on daily activities such as movement within the home, dressing, bathing, and perineal hygiene [1,2]. In addition, it may interfere with loss of ambulation, joint contractures, pressure ulcers, and pain [3].…”
Section: Introductionmentioning
confidence: 99%
“…Two thirds of humans after SCI complain of pain; about a third of them perceive their pain as severe (Lui et al 2015). It is therefore reasonable to assume the same in dogs (Lorenz et al 2011).…”
Section: Pain and Spasticitymentioning
confidence: 99%
“…Recent studies show that the principal cause of spasticity is a lesion of descending tracts resulting in the decreased activity of inhibitory interneurons, leading to excessive reactions of motoneurons to excitatory stimuli (Lewis and Olby 2017). In the management of spasticity, administration of baclofen, diazepam or dantrolene, chemodenervation by botulinum toxin, and laser or pulsed radiofrequency therapy deliver positive results (McIntyre et al 2014;Lui et al 2015;Chang and Cho 2017;Zielinska et al 2017). In spasticity resistant to conservative treatment, the interruption of reflex pathways by selective dorsal rhizotomy or myelotomy is recommended (Enslin and Fieggen 2016).…”
Section: Pain and Spasticitymentioning
confidence: 99%
“…Neuromuscular blockade via injection of alcohol is frequently used to reduce the tone of overactive muscles in clinical practice (10)(11)(12). The effect of a nerve block using alcohol can be influenced by the: volume and concentration of injectate; selection of block site; localization of the target nerve; and dispersion of the injectate (13).…”
mentioning
confidence: 99%